NeiyiKangfu tablets control the progression of endometriosis through inhibiting RAF/MEK/ERK signal pathway by targeting RKIP. (2nd December 2022) - Wen, Yi; Fan, Lingxiu; Pang, Lili; Zhao, Tingting; Li, Ruonan; Zhang, Ying; Zhang, Liye; Yang, Wei
Abstract: Background: NeiyiKangfu tablets (NYKF) are widely used clinically for the treatment of endometriosis (EMS), whose mechanism of action has been extensively studied. Researchers have found that NYKF may control the development of ectopic lesions by inhibiting angiogenesis and inflammatory cytokine secretion. Nevertheless, NYKF's mechanism of action remains unclear. Methods: In the present study, the function of NYKF in the progression of EMS and the associated underlying mechanism was investigated by in vivo and in vitro experiments. EMS model mice were treated with NYKF and the pro-inflammatory factors and apoptosis of ectopic endometrium as well as RAF/mitogen-activated protein kinase kinase (MEK)/extracellular signal-regulated kinase (ERK) signaling activation were assessed. In addition, human endometriosis-derived immortalized entopic stromal (hEM15A) cells transfected with or without RAF kinase inhibitor protein (RKIP)-small-interfering RNA (siRNA) were also treated with NYKF and the proliferation, migration, apoptosis, and RAF/MEK/ERK signaling activation were measured by Cell Counting Kit-8 (CCK-8), flow cytometry, Transwell, and western blot, respectively. Results: Results showed that NYKF increased the expression of RKIP, inhibited RAF/MEK/ERK signaling activation, and induced apoptosis while inhibiting proliferation and migration both in EMS mice and hEM15A cells. RKIP knockdown could inhibit the effect of NYKF treatment, leading to the activation of RAF/MEK/ERK signaling and the proliferation and migration of hEM15A cells. Conclusions: In conclusion, these results suggest that NYKF treatment promotes apoptosis and inhibits proliferation and migration in EMS by inhibiting the RAF/MEK/ERK signaling pathway by targeting RKIP.